Politics of Body and Writing the Self: Female Resistance and Self-Exploration in Margaret Atwood’s Surfacing - Mehmood, Amina; Abbas, Warda; Azam, Sarah (Pakistan Languages and Humanities Review, 2024)
This research seeks to address the politics of female body and writing the ‘self’ in Margaret Atwood’s Surfacing. This study highlights the trope of feminine writing by discussing the significance of female body which is suppressed/colonized and suffers from identity crisis but reclaims itself by finding self-expression through body. By drawing upon the theoretical concepts of Helene Cixous’s “Ecriture Feminine”, it engages with the phenomenon that when a female body suffers from oppression and violence, it defies the patriarchal structures of phallocentric language and constructs its own mode of resistance by writing through body which helps a woman find means to explore her lost self. The textual analysis demonstrates that the individual self of the female protagonist gets divided and bears psychic traumas which ultimately lead her towards resistance. Hence, the reclamation of self becomes an inevitable quest for the protagonist which she endeavors to explore and ultimately achieves it.